AGGREGATE-FORMATION MECHANISM OF NATURAL AND SYNTHETIC POLYMER FLOCCULANTS AND A COMPARATIVE ANALYSIS OF THEIR EFFICIENCY IN INDUSTRIAL WASTEWATER TREATMENT (Symposium on Natural and Applied Sciences, 2026)
This thesis compares the aggregate-formation mechanisms of natural and synthetic polymer flocculants and their efficiency in industrial wastewater treatment. Synthetic polyacrylamide (PAA) and sodium polyacrylate, together with modified natural-based polyacetylcellulose (PAC) and KMS, were studied. High-molecular-mass PAA formed large, strong flocs mainly by a bridging mechanism, whereas anionic sodium polyacrylate exhibited a charge-patch mechanism. Natural flocculants are environmentally safe but produce smaller and looser flocs. Owing to synergism, the composite system (PAA + sodium polyacrylate + PAC + KMS) provided the largest floc size (d₅₀ ≈ 820 μm) and 98.6 % turbidity removal. In settling velocity and residual turbidity the composite system surpassed all individual reagents.
Keywords: flocculant, polyacrylamide, sodium polyacrylate, polyacetylcellulose, bridging mechanism, charge patch, floc, settling velocity, synergism, wastewater.